Features of pyelonephritis course in adolescent females with co-existing anаemic syndrome - I.S. Lembryk; I.V. Shlimkevych; A.B. Stefanyshyn; O.V. Zhyliak; N.I. Kostyrko (Zaslavsky O.Yu., 2023)
Background. Anaemic syndrome of complex origin is not uncommon in urinary tract infection, particularly in dietary non-adherence, menstrual cycle disorders, or concomitant digestive diseases, recurrent respiratory infections, etc. However, there is currently insufficient epidemiological data on this comorbidity in the literature. This study aims to establish the features of pyelonephritis course in its combination with anaemic syndrome in children. Materials and methods. We analysed the medical records of 200 children aged 0 to 17 years with acute non-complicated pyelonephritis, complicated and recurrent urinary tract infections for 2012-2017. In the second stage of our work, we comprehensively examined 85 girls aged 11 to 17 who underwent inpatient treatment between 2018 and March 2023. Thirty children of the same age and gender made up the comparison group. A paediatric gastroenterologist, a paediatric gynaecologist and/or urologist examined all patients. Immunochemical method with electrochemiluminescence immunoassay was used to assess ferritin content; also, serum iron and total iron-binding capacity were measured. Results. Anaemic syndrome is common in most girls with urinary tract infections (58.8 % of сases). Among the causes, the following are distinguished: menstrual cycle disorders with abnormal uterine bleeding (50.0 %), chronic digestive disorders, in particular malabsorption syndrome of unknown origin (25.0 %), recurrent bronchopulmonary disorders (15.0 %), and unbalanced diet (10.0 %). The features of urinary tract infections and concomitant iron deficiency in children include fatigue (55.0 % in acute non-complicated pyelonephritis vs. 40.0 % in complicated urinary tract infections, р < 0.05), dizziness (35.0 % in acute non-complicated pyelonephritis vs. 15.0 % in recurrent urinary tract infections, χ2 = 48.6532, р < 0.05), and pallor (25.0 % in complicated urinary tract infections vs. 10 % in recurrent urinary tract infections, χ2 = 0.7168, р > 0.05). The ferritin level was the highest in patients with complicated urinary tract infections (18.2 µg/mL). In patients with recurrent urinary tract infections, this indicator was the lowest - 5.0 µg/mL. Conclusions. Retrospective analysis of medical records confirmed the presence of anaemia in 30.0 % of girls with inflammatory kidney diseases. During the physical examination, 58.8 % of female adolescents with urinary tract infections had signs of anaemic syndrome.